Dioxin distribution characteristics and health risk assessment in different size particles of fly ash from MSWIs in China. (April 2016) - Wu, Simiao; Zhou, Jizhi; Pan, Yun; Zhang, Jia; Zhang, Lingen; Ohtsuka, Nobutoshi; Motegi, Mamoru; Yonemochi, Shinichi; Oh, Kokyo; Hosono, Shigeo; Qian, Guangren
Highlights: Potential risk of dioxin in fine MSWI fly ash was evaluated as it was resuspended. Dioxin concentrations in Dp10–2.5 and Dp2.5 were higher than those in bulk ash. PCDF congener and homologues were the dominant contributors to the total TEQ. Finer particle fly ash posed higher carcinogenic risk on onsite workers. Abstract: During the process of treating and recycling Municipal Solid Waste Incinerators (MSWIs) fly ash, polychlorinated dibenzo-p-dioxins (PCDD/Fs) and polychlorinated dibenzofurans (dl-PCBs) in fly ash may potentially mobilize in the atmosphere and be widely distributed in the environment because of the inevitable re-suspension. Thus, this work presents the distributions of PCDD/Fs and dl-PCBs in inhalable coarse particles (Dp10–2.5 (particle diameter in μm)), fine particles (Dp < 2.5) of fly ash and original fly ash from four MSWI plants in China. The results show that PCDD/Fs and dl-PCBs preferentially concentrated in Dp10–2.5 and Dp < 2.5. Their mass concentrations and TEQ were significantly higher than those in the original fly ash, but the distribution of PCDD/Fs congeners in Dp10–2.5 and Dp < 2.5 was close to that in the original fly ash. The main TEQ contribution included 1, 2, 3, 7, 8-PeCDD, 2, 3, 7, 8-TeCDD in PCDDs and 2, 3, 4, 7, 8-PeCDF in PCDFs for Dp10–2.5, Dp < 2.5 fractions and the original fly ash. Furthermore, the mass and TEQ contribution of dl-PCBs was relatively low. In addition, compared with the fluidized bed, the samples from the grate-type furnaces had significantly lower dioxin concentrations. In terms of potential health risk, the non-carcinogenic risk of PCDD/Fs in Dp10–2.5 and Dp < 2.5 were estimated at 9.87 × 10 −1 to 4.81 and 1.19–7.95. For the carcinogenic risk of PCDD/Fs, both accumulation of Hazard Quotients (HQ) in Dp10–2.5 and Dp < 2.5 exceeded the threshold limit and should be considered as unacceptable risk for onsite workers. The above findings could provide data to support the risk management of MSWI fly ash during the process of recycle and disposal.